Spatio – temporal analysis of temperature in Erbil governorate using geographical information system (GIS) - Mohammed Tayeb Raoof; Tariq Khidr Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Temperature is considered one of the main and affective weather elements that have a direct impact on human activities and the natural environment. The purpose of this research is to distribute and analyze spatial and temporal temperatures and to determine the relationship between temperature and weather elements in Erbil Governorate during the period between (2002-2020), in each of (Makhmur, Koya, Erbil, Khabat, Pirmam, Shaqlawa, Soran, Mergasur) stations, conducting the regional analysis system and using (SPSS.V.26) (Excel) (Arc GIS.10.3) programs. The research concluded that there is a spatially and temporally significant difference in the average temperatures in the research area, as the highest average annual temperature in Makhmur station reached (22.8°) Celsius, and the lowest average temperature was recorded in Mergasur station, which amounted to (15.9°) Celsius, and with regard to the time difference, the highest average temperature was recorded in the year (2010) reaching (21.5°) Celsius, and the lowest temperature in the year (2019) was (18.6°) Celsius. In addition, as a result of applying statistical analysis regarding temperatures and rainfall in the research area, it turned out that there is a strong inverse relationship of (-0.855), and at the same time this relationship regarding actual sunlight and relative humidity was a weak inverse relationship which amounted to (-0.176/-0.117), only wind speed had a strong direct relationship reaching (0.619), and the relationship of altitude above sea level with temperature was a strong inverse relationship amounting to (-0.909).